1999
DOI: 10.1159/000026558
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fentanyl and Low Doses of Alcohol on Neuropsychological Performance in Healthy Subjects

Abstract: The effects of the opioid fentanyl and low doses of alcohol on neuropsychological functions in healthy volunteers were measured. Twenty-four healthy male volunteers participated in this study. Two randomised placebo-controlled cross-over trials were conducted. In group 1, 6 subjects received fentanyl (0.2 µg/kg body weight) in the order of fentanyl/placebo and 6 subjects in the order of placebo/fentanyl. Group 2 received alcohol in a similar procedure by continuous intravenous infusion, leading to a blood alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Twenty-one of 34 previous studies included multiple measures over various time spans that ranged from 8.1 min to 8.0 hr (see Koelega's review, 1995;Davidson et al, 1997;Millar et al, 1999;Mulvihill et al, 1997;Schneider et al, 1999;Swift et al, 1996;Wesnes et al, 2000). However, one third of the 21 studies did not report results of a timecourse evaluation, one third showed no effect of timecourse, and only one third showed an effect, or a trend for an effect, of alcohol across time.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-one of 34 previous studies included multiple measures over various time spans that ranged from 8.1 min to 8.0 hr (see Koelega's review, 1995;Davidson et al, 1997;Millar et al, 1999;Mulvihill et al, 1997;Schneider et al, 1999;Swift et al, 1996;Wesnes et al, 2000). However, one third of the 21 studies did not report results of a timecourse evaluation, one third showed no effect of timecourse, and only one third showed an effect, or a trend for an effect, of alcohol across time.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted cognitive control neural circuitry function is evident in a host of studies indicating cognitive and psychomotor impairments such as decrements in working memory, reduced cognitive flexibility, and increased impulsivity in long-term opioid users (Baldacchino, Balfour, Passetti, Humphris, & Matthews, 2012; Mintzer, Copersino, & Stitzer, 2005; Prosser, London, & Galynker, 2009; Verdejo, Toribio, Orozco, Puente, & Pérez-García, 2005; Zacny, 1995) and healthy, opioid-naïve individuals (Baldacchino, Balfour, Passetti, Humphris, & Matthews, 2012; Cherrier, Amory, Ersek, Risler, & Shen, 2009; Schneider et al, 1999; Walker & Zacny, 1999; Zacny, 1995). Deactivation in brain regions involved in executive function (e.g., anterior cingulate cortex, dorsolateral prefrontal cortex) following acute, single-dose opioid administration provides further mechanistic insight into the relationship between opioid use and cognitive impairment (Becerra et al, 2006; Jastrzab et al, 2012; Lee et al, 2012; Prosser et al, 2009).…”
Section: Neuropharmacologic Effects Of Acute Opioid Administrationmentioning
confidence: 99%
“…If the squares form a specifi c pattern the subjects have to press a response button. The test indicates speed of information processing and vigilance [24] .…”
Section: Description Of Tests Benton Visual Retentionmentioning
confidence: 99%